Evolutionary history and precipitation seasonality shape niche overlap in Neotropical bat–plant pollination networks - Liévano‐Latorre, Luisa Fernanda; Varassin, Isabela G.; Zanata, Thais B. (Biotropica, 2023)
Species interactions are one dimension of a niche. Niche overlap arises when two species share an interaction partner. In pollination systems, environmental and biotic factors affect niche overlap. Here, we explored the effects of climate seasonality, plant and bat richness, morphological traits, and phylogenetic distance in shaping the niche overlap of Neotropical bat–plant pollination networks. We examined a dataset of 22 bat–plant pollination networks in the Neotropical region. We measured niche overlap in bats and plants with the Morisita‐Horn index (ĈH) and used a SAR model to test the relationships between niche overlap and both abiotic and biotic factors. We found a lower niche overlap among bats in communities composed of phylogenetically distant bat species. Moreover, plant and bat overlap was lower in regions with higher precipitation seasonality. Our results indicate that climate seasonality and bat evolutionary history drive niche overlap in Neotropical bat–plant pollination interactions. These findings suggest that a higher precipitation seasonality promotes the emergence of temporal modules, which reduces niche overlap, likely due to seasonal species phenologies. Furthermore, the method used to record the interactions affects the degree of niche overlap. Interactions recorded with pollen samples tend to have higher niche overlap than direct observations. The responses of morphological traits and phylogenetic distances in bat niche overlap were uncoupled, suggesting an effect of historical processes independent of morphological traits. Our findings reinforce the importance of evolutionary history and ecological processes in imprinting patterns of interaction niche overlap. in Portuguese is available with online material RESUMO As interações de espécies são uma das dimensões do nicho. Nelas, a sobreposição de nicho ocorre quando duas espécies compartilham um parceiro de interação. Em sistemas de polinização, fatores ambientais e bióticos impactam a sobreposição de nicho. Neste trabalho, nós exploramos os efeitos da sazonalidade climática, riqueza de plantas e morcegos, atributos morfológicos e da história evolutiva como determinantes da sobreposição de nicho nas interações de polinização morcego‐planta no Neotrópico. Para isso, usamos 22 redes de polinização morcego‐planta na região Neotropical. Medimos a sobreposição de nicho de morcegos e plantas usando o índice de Morisita‐Horn (ĈH), e usamos modelos SAR para testar as relações entre a sobreposição de nicho e os fatores abióticos e bióticos. Encontramos que a sobreposição de nicho foi menor em comunidades compostas por espécies de morcego distantes evolutivamente. Também encontramos que a sobreposição de nicho de plantas e morcegos foi menor em regiões com maior sazonalidade da precipitação. Nossos resultados indicam que a sazonalidade climática e a história evolutiva dos morcegos determinam a sobreposição de nicho nas interações de polinização de morcegos e plantas Neotropicais. Isso sugere que uma maior sazonalidade de precipitação pode promover o surgimento de módulos temporais como resultado das fenologias sazonais das espécies, o que causa uma redução na sobreposição de nicho. Além disso, o método usado para registrar a interação impacta o grau de sobreposição de nicho. As interações registradas com amostras de pólen tendem a ter uma maior sobreposição de nicho do que as observações diretas. As respostas desacopladas dos atributos morfológicos e das distâncias evolutivas na sobreposição de nicho dos morcegos sugerem um efeito dos processos evolutivos independente dos atributos morfológicos. Nossos resultados reforçam a importância da história evolutiva e dos processos ecológicos na impressão de padrões na sobreposição de nicho nas interações. Plant‐animal interactions are one dimension of niche. We measured niche overlap in Neotropical bat‐plant pollination interactions. Our findings reinforce the importance of evolutionary history and ecological processes in imprinting patterns of interaction niche overlap.